Development of a Remote‐Controlled Implantable Rat Sacral Nerve Stimulation System. Issue 6 (22nd October 2018) - Langlois, Ludovic; Antor, Marlène; Atmani, Karim; Le Long, Erwan; Merriaux, Pierre; Bridoux, Valérie; Dechelotte, Pierre; Leroi, Anne Marie; Meleine, Mathieu; Gourcerol, Guillaume
Abstract : Objectives: Sacral nerve stimulation (SNS) is a surgical treatment of urinary and fecal incontinence. Despite its clinical efficacy, the mechanisms of action of SNS are still poorly known. This may be related to the use of acute stimulation models. Up to date, no rodent model of chronic SNS implants has been developed. Therefore, the aim of this study was to create a fully implantable and remotely controllable stimulating device to establish an animal model of chronic SNS. Materials and Methods: The stimulating device consisted of an implantable pulse generator linked to a platinum electrode. The communication with the device was made through an inductive link which allowed to adjust the stimulation parameters; that is, to turn the device on and off or check the battery status remotely. Rats underwent two surgical procedures. In the first procedure, we achieved chronic sacral stimulation but the implanted electrode was not fixated. In the second procedure, the electrode was fixated in the sacral foramen using dental resin. In both cases, the correct positioning of the electrode was evaluated by computed tomography (CT) imaging and the presence of tail tremor in response to high intensity stimulation. We only tested the function of implanted electrode with fixation using micturition frequency assessment following bipolar or unipolar SNS for three days after recovery. Results: CT imaging showed that implantation of the electrode required fixation as we found that the second surgical procedure yielded a more precise placement of the implanted electrode. The correct placement of implanted electrode observed with imaging was always correlated with a successful tail tremor response in rats, therefore we pursued our next experiments with the second surgical procedure and only assessed the tail tremor response. We found that both bipolar and unipolar SNS reduced micturition frequency. Conclusion: This stimulating device provides an efficient method to perform chronic SNS studies in rats.